TRANSFORMING THE BANKING SYSTEM OF OUR COUNTRY WAYS TO IMPROVE THE MECHANISM (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
It is known that in recent years consistent reforms have been carried out in the banking and financial system in our country, a number of measures have been implemented, and as a result, the necessary legal conditions have been created to provide advanced banking services and strengthen the competitive environment in this system.